PERSONAGENS CONCEITUAIS COMO ESTRATÉGIA PARA O ENSINO DE FILOSOFIA: UMA PROPOSTA A PARTIR DE DELEUZE E GUATTARI - MENSSIOS LEONI ARAUJO ELOY (2024)
Based on the work entitled What is Philosophy?, by Gilles Deleuze and Félix Guattari, in which the authors explain that philosophical constructionism occurs through three interrelated activities (tracing a plane of immanence – creating concepts – inventing characters ), this dissertation is about the use of conceptual characters in the teaching of philosophy, as a strategy to be used in the classroom. The work is developed in four sequential parts that deal, respectively, with the following subjects: how philosophical concepts are constructed; how plans of immanence are drawn by philosophers; the presence of conceptual characters in strict relationship with the plans and concepts; an example based on the analysis of the Rousseauian Legislator, as a conceptual character. From these points, the importance of conceptual characters in philosophical constructivism and the possibility of them being more widely used in philosophy teaching is affirmed.